The Effect of Intraspinal Micro Stimulation With Variable Stimulating Pattern in Adult Rat With Induction of Spinal Cord Injury in the Treatment of Spinal Cord Injuries - Hedayatzadeh, Mohaddeseh; Kobravi, Hamid Reza; Tehranipour, Maryam (International Clinical Neuroscience Journal, 2019)
Background: Spinal cord injury is one of the diseases that, no specific treatment has yet found despite the variety of works that have done in this field. Different approaches to treat such injuries have investigated today. One of them is invasive intra-spinal interventions such as electrical stimulation. Therefore, in this study, the effect of the protocol for intra-spinal variable and fixed electrical stimulation has been investigated in order to recover from spinal cord injury. Methods: In the study, 18 Wistar male rats randomly divided into Three groups, including intra-spinal electrical stimulation (IES), IES with variable pattern of stimulation (VP IES) and a sham group. Animals initially subjected to induced spinal cord injury. After one week, the animal movement was recorded on the treadmill during practice using a camera and angles of the ankle joint were measured using the Tracker software. Then, the obtained data were analyzed by nonlinear evaluations in the phase space. Results: The motion analyses and kinematic analyses were carried out on all groups. According to the achieved results, the gait dynamics of the VP IES group has the most conformity to the gait dynamics of the healthy group. Also, the best quality of the balance preservation observed in the VP IES group. Conclusion: It can be concluded that the IES with variable pattern of stimulation along with exercise therapy has significant gait restorative effects and increases the range of motion in rats with induced spinal cord injury.